Pengaruh Capital Adequacy Ratio Dan Financing To Deposit Ratio Terhadap Return On Asset Pada PT. Bank Muamalat Indonesia, Tbk - Elsy (LPPM STIE Tri Dharma Nusantara - Makassar, 2025)
This research aims to determine the effect of Capital Adequacy Ratio and Financing to Deposit Ratio on Return on Assets at PT. Bank Muamalat Indonesia, Tbk. The types of data used in this research are qualitative data and quantitative data. The data source used in this research is secondary data. The analytical method used is multiple linear regression, coefficient of determination, correlation coefficient, and t test f test. The results of the multiple linear regression equation with the equation value Y = 0,434 + 0,008X1+ 0,005X2, coefficient of determination (R2) of 74,6% and correlation coefficient (r) of 0,864. Thus it can be concluded that simultaneously the Capital Adequacy Ratio and Financing to Deposit Ratio have a significant effect on Return on Assets at PT. Bank Muamalat Indonesia, Tbk. Partially, the Capital Adequacy Ratio has a positive and significant effect on Return on Assets at PT. Bank Muamalat Indonesia, Tbk and partially the Financing to Deposit Ratio have a positive and significant effect on Return on Assets at PT. Bank Muamalat Indonesia, Tbk.